Use of castor bean polymer in developing a new technique for tibial tuberosity advancement for cranial cruciate ligament rupture correction in dogs - Medeiros, R. M. [UNESP]; Silva, M. A. M.; Teixeira, P. P. M.; Dias, L. G. G. G. [UNESP]; Chung, D. G. [UNESP]; Zani, C. C. [UNESP]; Feliciano, M. A. R. [UNESP]; Da Conceicao, M. E. B. A. M. [UNESP]; Machado, M. R. F. [UNESP]; Rocha, A. G. [UNESP]; Chierice, G. O.; Coutinho, L. N.; et al. (Czech Academy Agricultural Sciences, 2016)
The purpose of the current study was to develop a new tibial tuberosity advancement (TTA) technique, by replacing the original titanium cage with a Ricinus communis polyurethane resin-made wedge polymer. The implants were manufactured using the same size and angles of the original titanium cages, though larger distally. The modified TTA technique (TTAm) was performed in 42 knees of 35 dogs diagnosed with rupture of the cranial cruciate ligament (RCCL). Animals were submitted to radiographic and gait assessments preoperatively, early postoperatively and following 30, 60, 90 and 120 days. All animals exhibited good clinical outcome. There were no cases of impaired healing or bone resorption until 120 days postoperatively and there was no patient with patellar distress after TTAm. Scores of gait evaluation revealed differences between time points. There were also differences between the evaluations of control and pre- and post-operative times. However, there was no difference among the assessment of 30 days and the following time points. The use of the polyurethane polymer for TTAm was advantageous, not only due to biocompatibility and osseointegration, but also for providing easy handling; it can be moulded intra-operatively if necessary. Moreover, it allows precise adaptation to the osteotomy site, as opposed to the original TTA metallic implants, which cannot be moulded. It is suggested that incision lengths for TTAm are slightly shorter than those required for the conventional TTA as this requires the distal fixation of the plate at the beginning of the middle third of the body of the tibia. The TTAm does not require the use of fixation plates and it is performed only at the cranial aspect of the tibia. The method of attachment of the tibial tuberosity in the craniocaudal direction was effective. The setting associated with the use of the polyurethane polymer allowed simplification of the technique for easier implementation, and the amount of implant material required to perform TTAm was reduced in comparison to the conventional TTA. This technique can be used for treating the knees of dogs with RCCL, and provides for easy execution, less invasiveness to the tissues of the knee joint and more versatility in comparison to conventional TTA.
Keywords: orthopaedic implant; corrective osteotomy; knee; ligament tear; canine